Modeling and simulation of the Vigor wave energy converter - Thorbergsson, Egill (Chalmers tekniska högskola / Institutionen för tillämpad mekanik, 2009)
The need to make renewable energy a larger part in today’s electricity generation is increasing because of environmental issues and energy security. A potential resource of energy that is starting to attract more attention is the energy in ocean waves. There is no commercial approach available but a large number of applications are competing to be the first ones to enter the market. A new approach, which was invented by Daniel Ehrnberg, has showed good potential. The approach is still in the design phase and a number of problems are still unsolved. In this thesis two problems are tackled; the interaction of the device and the ocean, and how to calculate the power output of the device. The solution to the first problem shows how the device will react to ocean waves. The solution to the second problem gives an idea of the energy potential of the device. The potential energy output of the the device is calculated for four different locations; two in Iceland, one in Ireland and Sweden. The conclusion is that the device can reach high efficiency of converting the wave energy into useful energy but works only when the waves are optimal for the device.